Correction: Li et al. Preliminary Evaluation of Protective Efficacy of Inactivated Senecavirus A on Pigs. Life 2021, 11, 157 - Yuwan Li; Yangyi Zhang; Yingxin Liao; Yawei Sun; Yang Ruan; Chenchen Liu; Mengru Zhang; Fangfang Li; Xiaowen Li; Shuangqi Fan; Lin Yi; Hongxing Ding; et al. (Life)
In the original publication, there was a mistake in Figure 1B(b,c) as published [...]